Флорентийка: роман : [перевод с французского] (Ж. Бенцони) - Бенцони Жюльетта (2001)
Экземпляры: АБ (20180608) / Инвентарный номер: 36918 / Цена: 37.50 / Сис.шифр: 84(4Фра) / Авт.знак: Б 46 / ББК: 84(4Фра)